The differences of the skeletal and dental heights between the two age groups of cl-ass I deep bite. (Cephalometric Study) - Hind T Jarjees; Ra'ed J Sa'id; Younis M Saeed (University of Mosul, College of Dentistry, 2007)
Aims: The purpose of this study was to determine the age differences for deep bite malocclusion concerning facial skeletal and dentoalveolar height. Materials and Methods: It was carried out on a sample of (50) students (16 males and 34 females), aged (12-15) years with class I deep bite malocclusion present when the incisal edge of the lower central incisor is at least in contact with the gingival third of the upper central incisor in normal healthy individuals with full set of permanent teeth in both jaws. The sample were divided into two age groups (12-13) and (14-15) years old. Lateral cephalometric radiograph was taken for each subject. Twenty-one cephalometric measurements (nine angular and twelve linear) and five ratios had been determined. The data were statistically analysed using statistical package for social statistics. Results: The results revealed that upper anterior facial height, ramus height, total posterior facial height, lower posterior facial height, upper posterior dental height and lower anterior dental height were significantly increase with age in total sample. Males showed increase of total posterior facial height and lower posterior facial height with age while females showed increase of lower posterior facial height and upper posterior dental height with increasing age. Concerning ratios, total posterior facial height to total anterior facial height ratio was increased significantly with age in males opposite to the lower anterior facial height to total anterior facial height ratio which was decreased significantly with age in males. Upper posterior dental height to upper anterior dental height ratio showed significant increase with age in males, females and total sample. Angular measurements revealed that males, females and total sample showed significant decrease of the angle formed by the intersection between occlusal plane and palatal plane (Occ-pp) with increasing age. Conclusions: Deep bite was affected by age only for posterior skeletal facial dimensions and not for anterior skeletal facial measurements.